Development Assistance for Africa as Part of the Chinese–American Rivalry - Zaremba, Michał (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
The system of development assistance for Africa in recent years has become one of the most important tools in the rivalry between world powers on the continent. Due to the increasingly important position in the global system of China which is now competing with traditional donors, the problems with development assistance are gaining in importance as a potential area for competition among global powers. The aim of the article is to analyze the development assistance of China and the United States for Africa as part of the these two superpowers’ global rivalry.